Factors Affecting Selenium Status in Infants on Parenteral Nutrition Therapy. Issue 3 (18th September 2021) - Rao, Anita; Jericho, Hilary; Patton, Tiffany; Sriram, Sudhir; Hebert, Taylor; Weinstein, Dana; Pompeii-Wolfe, Cecelia; Wroblewski, Kristen; Sentongo, Timothy
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Introduction: Selenium is an essential micronutrient that must be supplemented in infants and young children on exclusive parenteral nutrition (PN). We examined selenium status and clinical factors associated with a deficiency in infants on PN. Methods: This was a retrospective cohort study of pediatric patients receiving PN with routine monitoring of selenium status. Deficiency was diagnosed using age-based norms of plasma selenium status. Associations between selenium deficiency and the following clinical factors were examined: birthweight status: extremely low birthweight (ELBW) versus very low birthweight (VLBW) versus low birthweight (LBW) versus normal birthweight (NBW), serum albumin status, presence of cholestasis, and co-administration of enteral feeds. Results: A total of 42 infants were included with gestational age [median (interquartile range)] 28 weeks (25, 34) . The prevalence of selenium deficiency was 80% and the prevalence of albumin deficiency was 87.5%. The odds of selenium deficiency were higher in ELBW infants (odds ratio = 17.84, 95% confidence interval [4.04–78.72], P  < 0.001) and VLBW infants (odds ratio = 16.26, 95% confidence interval [1.96–135.04], P  < 0.001) compared to NBW infants. The odds of selenium deficiency were 5-fold higher in patients with low serum albumin (odds ratio = 5.33, 95% confidence interval [1.39–20.42], P = 0.015). There were no associations seen between selenium status and presence of cholestasis or co-administration of enteral feeds. Conclusion: In this cohort of infants on PN therapy, the main clinical factors associated with selenium deficiency were presence of hypoalbuminemia and history of ELBW or VLBW. These findings support dual measurement of serum albumin and serum selenium to improve interpretation of selenium status.